Chemical reaction characteristics, structural transformation and electrochemical performances of new cathode LiVPO4F/C synthesized by a novel one-step method for lithium ion batteries. Issue 13 (13th February 2018) - Li, Qiyuan; Wen, Zheng; Fan, Changling; Zeng, Taotao; Han, Shaochang
Abstract : Uniform LiVPO4 F/C primary particles and lattice coated with carbon layer forms at 800 °C. Larger impurity Li3 V2 (PO4 )3 /C particles are generated at 850 °C. Abstract : A new cathode LiVPO4 F/C with a high working voltage of around 4.2 V was synthesized by a novel one-step method. The color of the solution turns green, which implies that V2 O5 is successfully reduced to V 3+ . The reaction thermodynamics indicates that LiVPO4 F/C is formed when the sintering temperature is higher than 650 °C, while the accompanying impurity phase Li3 V2 (PO4 )3 /C is also generated. The reaction kinetics proves that the reaction is third order and the activated energy is 208.9 kJ mol −1 . X-ray photoelectron spectra imply that the components of LiVPO4 F/C prepared at 800 °C (LVPF800) are in their appropriate valence. LVPF800 is composed of micron secondary particles aggregating from nano subglobose. The structural transformation shows that the V : P : F ratio in LVPF800 is close to 1 : 1 : 1. The reason behind generation of impurity Li3 V2 (PO4 )3 at a high temperature of 850 °C is demonstrated directly, which is mainly due to the volatilization of VF3 . The electrochemical performances of the cathode are related to the crystallite content of LiVPO4 F/C and Li3 V2 (PO4 )3 /C. The specific capacities at 0.2 and 5C of LVPF800 are as high as 139.3 and 116.5 mA h g −1 . Electrochemical analysis reveals that LVPF800 possesses an excellent reversibility in the extraction and insertion process and minimum charge transfer resistance.